Determinants of sustainable development among Malaysian small and medium enterprises / Mohd Najib Saad and Mazlina Manshor - Saad, Mohd Najib; Manshor, Mazlina (UiTM Press, 2023)
Sustainable development is an emerging paradigm designed to strike the balance between the ecological health of the planet and human development in a manner which ensures that both meet the needs of the present without compromising the future. However, little is known about the determinants of sustainable development among Small and Medium Enterprises (SMEs) in Malaysia. As such, the present study fills up the gaps by examining relationship between integrated management systems, technology and innovation capability, sustainability orientation, green corporate image, government support and sustainable development. A quantitative survey was done on Malaysian SMEs. Data collected were analyzed using smartPLS 3.0. The present study discovered that technology and innovation capability, sustainability orientation and green corporate image had significant effects on sustainable development. However, integrated management systems and government support were insignificant.